Radiological environmental monitoring program national level: Results 2009 - Osores, José (2011)
The annual report of the results of the environmental radiation monitoring program developed in 2009 is presented, including also historical data to provide a frame of reference. This document is a continuation of the Environmental Radiation Monitoring Program developed by the Peruvian Institute of Nuclear Energy (IPEN) since 1990 and shows information on environmental radioactivity levels in the country available for public and private organisms as well as for general public. This paper briefly describes the main features of the environmental radiation monitoring programs in the Peruvian territory their results obtained from the surveillance campaign of 2009. It also shows the temporal radiological projection values more representatives in the recent years.